16S rRNA Gene Sequence Analysis of V6–V8 Region Provides Limited Advantage in Diagnosis of Chronic Prostatitis - Jens Rosellen; Moritz Fritzenwanker; Hans-Christian Schuppe; Undraga Schagdarsurengin; Florian Wagenlehner; Adrian Pilatz (Diagnostics)
Background: 16S rRNA analysis has been used in various diseases to identify pathogenic bacteria. In particular, pathogens that are difficult to cultivate or previously unknown can be detected with great certainty. In chronic prostatitis/chronic pelvic pain syndrome (CP/CPPS), a distinction between bacterial and non-bacterial genesis is essential with regard to categorization and therapy. The objective of this study is to investigate the value of 16S rRNA gene sequence analysis in the routine management of patients with CP/CPPS especially after failure to detect a pathogen in conventional culture and polymerase chain reaction for sexually transmitted diseases (STI-PCR). Methods: In total, 228 patients with CP/CPPS were prospectively enrolled and received a comprehensive andrological work-up. Microbial analysis consisted of standard bacterial cultures and the detection of sexually transmitted pathogens by PCR using urine specimens from a 2-glass test and semen analysis. 16S rRNA gene sequence analysis was performed in patients with urine and semen of patients without bacterial pathogens in microbiological culture and STI-PCR. Results: In 184 of 199 (92%) patients with negative ejaculate culture and negative STI-PCR, no pathogen could be detected by 16S rRNA analysis and in the case of a positive result, the analysis only showed non-pathogenic bacteria of the normal flora. There was no statistical association between the 16S rRNA analysis and the inflammatory markers or the National Institutes of Health Chronic Prostatitis Symptom Index (NIH-CPSI) scores. Conclusions: At least in our study cohort, the 16S rRNA analysis provided no additional benefit following microbiological culture and STI-PCR in the categorization of patients with CP/CPPS.